2021
DOI: 10.21203/rs.3.rs-674445/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of cannabis ingestion on endometriosis-associated pelvic pain and related symptoms.

Abstract: Background The use of cannabis for symptoms of endometriosis was investigated utilising retrospective archival data from Strainprint Technologies Ltd., a Canadian data technology company with a mobile phone application that tracks a range of data including dose, mode of administration, chemovar and their effect on various self-reported outcomes, including pelvic pain. Methods A retrospective, electronic record-based cohort study of Strainprint™ users with self-reported endometriosis was conducted. Self-rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Similarly people with endometriosis in Australia and New Zealand reported substantial substitution effects (>50% reduction in dose) in non‐opioid analgesia (63.1%), opioid analgesia (66.1%), hormonal therapies (27.5%), anti‐neuropathics (61.7%), antidepressants (28.2%) and anxiolytic medications (47.9%) 18 . A retrospective cohort study 19 on data collected using the Strainprint app among North American legal therapeutic cannabis users found that pelvic pain (42.4% of all participants) was the primary clinical indication for use of cannabis. Medicinal cannabis had a significant reduction on pelvic pain severity, with an efficacy rating of 31.98 (95% CI 31.26–32.71, P < 0.0001), 19 roughly equivalent to 20 mm on a 100 mm visual analogue scale, exceeding the minimum clinically important difference for endometriosis and consistent with other cohort studies 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly people with endometriosis in Australia and New Zealand reported substantial substitution effects (>50% reduction in dose) in non‐opioid analgesia (63.1%), opioid analgesia (66.1%), hormonal therapies (27.5%), anti‐neuropathics (61.7%), antidepressants (28.2%) and anxiolytic medications (47.9%) 18 . A retrospective cohort study 19 on data collected using the Strainprint app among North American legal therapeutic cannabis users found that pelvic pain (42.4% of all participants) was the primary clinical indication for use of cannabis. Medicinal cannabis had a significant reduction on pelvic pain severity, with an efficacy rating of 31.98 (95% CI 31.26–32.71, P < 0.0001), 19 roughly equivalent to 20 mm on a 100 mm visual analogue scale, exceeding the minimum clinically important difference for endometriosis and consistent with other cohort studies 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort study 19 on data collected using the Strainprint app among North American legal therapeutic cannabis users found that pelvic pain (42.4% of all participants) was the primary clinical indication for use of cannabis. Medicinal cannabis had a significant reduction on pelvic pain severity, with an efficacy rating of 31.98 (95% CI 31.26–32.71, P < 0.0001), 19 roughly equivalent to 20 mm on a 100 mm visual analogue scale, exceeding the minimum clinically important difference for endometriosis and consistent with other cohort studies 13 . Adverse events with medicinal cannabis, apart from cannabis hyperemesis syndrome, tend to be mild and self‐limiting, and include euphoria, orthorexia, sedation, dry mouth and lethargy 11,14 …”
Section: Introductionmentioning
confidence: 99%